Are the class 18 myosins Myo18A and Myo18B specialist sarcomeric proteins? - Horsthemke, Markus; Arnaud, Charles-Adrien; Hanley, Peter J. (Frontiers in Physiology, 2024)
Initially, the two members of class 18 myosins, Myo18A and Myo18B, appeared to exhibit highly divergent functions, complicating the assignment of class-specific functions. However, the identification of a striated muscle-specific isoform of Myo18A, Myo18Aγ, suggests that class 18 myosins may have evolved to complement the functions of conventional class 2 myosins in sarcomeres. Indeed, both genes, Myo18a and Myo18b, are predominantly expressed in the heart and somites, precursors of skeletal muscle, of developing mouse embryos. Genetic deletion of either gene in mice is embryonic lethal and is associated with the disorganization of cardiac sarcomeres. Moreover, Myo18Aγ and Myo18B localize to sarcomeric A-bands, albeit the motor (head) domains of these unconventional myosins have been both deduced and biochemically demonstrated to exhibit negligible ATPase activity, a hallmark of motor proteins. Instead, Myo18Aγ and Myo18B presumably coassemble with thick filaments and provide structural integrity and/or internal resistance through interactions with F-actin and/or other proteins. In addition, Myo18Aγ and Myo18B may play distinct roles in the assembly of myofibrils, which may arise from actin stress fibers containing the α-isoform of Myo18A, Myo18Aα. The β-isoform of Myo18A, Myo18Aβ, is similar to Myo18Aα, except that it lacks the N-terminal extension, and may serve as a negative regulator through heterodimerization with either Myo18Aα or Myo18Aγ. In this review, we contend that Myo18Aγ and Myo18B are essential for myofibril structure and function in striated muscle cells, while α- and β-isoforms of Myo18A play diverse roles in nonmuscle cells.